The Codex Visionum and the Uses of Greek Christian Poetry - Laura Miguélez-Cavero (Literature, 2023)
A systematic socio-cultural study of the uses of Christian poetry in the late antique Greek-speaking Mediterranean is still lacking. Most literary overviews restrict themselves to an overview of the extant texts and some programmatic reflections in the poetry by Gregory of Nazianzus. This paper seeks to address this matter by a combined reading of the best-known poetic forms (including the programmatic reflections by Gregory) and the poems copied in the Codex Visionum (now in the Bodmer Collection). Since the edition of the latter was completed in 1999, they have often featured in studies on the origin of monasticism and are well known in papyrological circles, but have received insufficient attention from literature and cultural historians.